The Effects of the COVID-19 Pandemic on Trends and Types of Pediatric Burn Injuries: Lessons from a National Burn Center and the Role of Strategic Resource Allocation - Raluca Tatar; Dan Mircea Enescu; Doina Iulia Nacea; Gabriela Viorela Nițescu; Andreea Lescaie; Mihaela Pertea; Petruța Mitrache; Laura Sorina Diaconu (Life)
The COVID-19 pandemic had a huge global impact on healthcare systems that affected all medical services, including burn care facilities. This paper analyzes the effects of this medical crisis on pediatric burn injuries by comparing patient data from 2019 (pre-pandemic) and 2020 (during the pandemic) at a national burn center in Romania. The study included, overall, 676 patients, out of which 412 were admitted in 2019. In 2020, the admissions decreased by 35.9% (n = 264). However, moderate and severe burns remained constant and burn severity increased in 2020, with a larger total body surface area affected on average. Surgical management rates and hospital stay duration increased in 2020 from 18% to 39% and from 7 days to 11 days, respectively. Admissions to the intensive care unit and mortality rates remained similar between 2019 and 2020. Scalds were the leading cause of burns in both years; however, in 2020, they affected a larger total body surface area. Contact burns decreased significantly in 2020 from 10.9% to 5.2%, likely due to reduced outdoor activities. The concomitant presence of SARS-CoV-2 infection and burn injuries did not have a negative impact on complication rates, surgical management approaches, or duration of hospitalization. These findings emphasize the need to preserve dedicated burn care human and material resources during global health crises in order to offer access to the best quality of care, thus ensuring optimal patient outcomes, regardless of fluctuations in admission rates.